PERBEDAAN PEMBERIAN INTERVENSI NUTRISI SELAMA SATU TAHUN PERTAMA KEHIDUPAN PADA BATITA STUNTING DAN TIDAK STUNTING DI WILAYAH KERJA PUSKESMAS SUMBER KABUPATEN CIREBON - Widad Fadiyah; Dewi Erna Marisa; Ika Nurfajriyani (Jurnal Kesehatan Mahardika, 2020)
Self efficacy is a belief held by patients with chronic kidney failure undergoing hemodialation. Compliance with hemodialysis is the behavior of patients in the form of adherence to undergo hemodialysis. Chronic kidney failure is a progressive and irreversible disruption of renal function in which the body's ability to fail to maintain metabolism and fluid and electrolyte balance, causes uremia (retention of urea and other nitrogenous wastes in the blood). This study aims to determine the relationship of self efficacy with adherence to undergo hemodialysis in patients with chronic kidney failure who undergo hemodialysis in Waled District Hospital Cirebon, 2020.  This research method uses descriptive correlational with cross sectional approach. The population was patients with chronic renal failure who underwent hemodialysis at Waled District Hospital Cirebon as many as 128 patients and the sampling technique using purposive sampling technique obtained 57 respondents. The instrument used in the form of a questionnaire sheet, and data analysis using the Spearman rank test, the significance value α = 0.05.  The results showed that self efficacy with a low category was (61.4%) and compliance underwent hemodialysis with an adherent category of (54.5%). There is a relationship between self-efficacy and compliance with hemodialysis in chronic renal failure patients undergoing hemodialysis at Waled Hospital, Cirebon Regency. Respondents with high self-efficacy have a high level of compliance with hemodialysis. Nutrition education and stunting prevention need to be given since pregnancy planning in couples of childbearing ages. Growth monitoring need to be carried out continuously since the beginning of the baby's life and nutrition need to be adjusted according to established guidelines.